(untitled) (Bangladesh Journal of Urology, 2020)
Purpose: To observe the outcome of single stage buccal mucosal graft and Johanson’s staged urethroplasty for treatment of pan- urethral stricture. Materials and Methods: A total of 60 patients with an average age of 42 years (21-55) underwent OMG urethroplasty and Johanson’s staged urethroplasty between March 2008 to September 2015 for pan-urethral stricture of different etiology. OMG was always harvested from cheek using 2 team approaches. Graft was placed using Kulkarni technique. Clinical outcome was considered success or failure if any post operative procedure needed. Mean follow up was 45 month (6-95) Results: Total 60 patients were included for final calculation, 31 patients with buccal mucosal graft (Group A) and 29 patients with Johanson’s staged urethroplasty (Group B) were followed up for average 45 months. Success rate of group A was 93.5% at 3 months and 77.4% at 3 years and in group B 65.5% at 3 months and 44.8% at 3 years follow up which is statiscally significant (p <.05). Postoperative complications were significantly higher in group-B. Conclusion: Repair of pan-urethral stricture in a single-stage OMG by Kulkarni technique is simple, fast, safe, effective and reproducible in the hand of any surgeon. Bangladesh Journal of Urology, Vol. 19, No. 2, July 2016 p.78-84